1983
DOI: 10.1098/rstb.1983.0034
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphorylation and the control of glycogen metabolism in skeletal muscle

Abstract: Glycogen metabolism in mammalian skeletal muscle is controlled by a regulatory network in which six protein kinases, four protein phosphatases and several thermostable regulatory proteins determine the activation state of glycogen phosphorylase and glycogen synthase, the rate-limiting enzymes of this process. Thirteen phosphorylation sites are involved, twelve of which have been isolated and sequenced and shown to be phosphorylated in vivo . The effects of adrenalin and insulin on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…The Western blot (from the 2D gel) performed on material from non-regenerating arms further suggested that this TGF-β-like molecule might exist in at least two isoforms. The close proximity of the isoforms to each other implies that they could result from a single posttranslational modification such as phosphorylation (Cohen 1983;Massagué 1998). During regeneration, significant changes in this profile are evident.…”
Section: Discussionmentioning
confidence: 98%
“…The Western blot (from the 2D gel) performed on material from non-regenerating arms further suggested that this TGF-β-like molecule might exist in at least two isoforms. The close proximity of the isoforms to each other implies that they could result from a single posttranslational modification such as phosphorylation (Cohen 1983;Massagué 1998). During regeneration, significant changes in this profile are evident.…”
Section: Discussionmentioning
confidence: 98%
“…En effet, parmi les méthodes biochimiques permettant d'étudier le métabolisme musculaire au cours de la contraction, celles se rapportant soit à la détermination du quotient respiratoire (rapport C0 2 libéré/0 2 absorbé), soit aux modifications des substrats endogènes ou à l'utilisation des substrats exogènes in vivo et in vitro ont montré leurs limites techniques : difficulté des mesures de substrats spécifiques (entre différents glucides par exemple), difficulté de quantifier des substrats phosphorylés ou non, catabolisés rapidement au cours du prélèvement de l'échantillon musculaire (Corsi et al, 1969). Les Stetten, 1960 ;Cohen, 1983). Toutefois, des études plus récentes montrent que la glycogénolyse n'aurait un rôle important qu'au début de l'activité physique en produisant un surplus d'ATP, ou lorsque l'énergie néces-saire à l'accomplissement de travaux musculaires intenses excède celle produite par l'utilisation des acides gras et autres substrats circulants (Rowell etal., 1966 ;Bergstrôm et al, 1967 ;Havel, 1970 ;Beatty et al, 1972 ;Newsholme et al, 1978).…”
Section: A) Propriétés Des Fibres Musculairesunclassified
“…The dephosphorylated form (I form) is spontaneously active and virtually independent from the allosteric activation by glucose-6-phosphate (G6P);' the phosphorylated form (D form) is inactive and sensitive to the action of the allosteric activator, G6P. The change from the dephosphorylated to the phosphorylated state is carried out by several protein kinases (5,6); the inverse reaction is catalyzed by glycogen synthase phosphatase (protein phosphatase) (7). Insulin enhances glycogen synthase activity by a mechanism involving the activation of glycogen synthase phosphatase (8)(9)(10) and the inhibition of cAMP-dependent protein kinase (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen synthase is the rate-limiting enzyme for glycogen synthesis (4). Its activity can be modulated by allosteric or covalent (phosphorylation or dephosphorylation) modifications of the molecule (5,6). The dephosphorylated form (I form) is spontaneously active and virtually independent from the allosteric activation by glucose-6-phosphate (G6P);' the phosphorylated form (D form) is inactive and sensitive to the action of the allosteric activator, G6P.…”
Section: Introductionmentioning
confidence: 99%